PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 008 PEMATANG SEMUT - Safriyandi Safriyandi; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The study was motivated by the low results of social studies class V students of SD Negeri 008 Pematangsemut with an average value of 60.23 out of 23 students. The problems of this research whether the implementation of cooperative learning model Numbered Head Together (NHT) can improve learning outcomes IPS fifth grade students of SD Negeri 008 Pematangsemut? The purpose of this study is to improve student learning outcomes through the implementation of IPS-type cooperative model Numbered Head Together (NHT) in class V SD Negeri 008 Pematangsemut. Research was conducted in the second semester of 2015/2016 school year in April and May 2016. The subjects were fifth grade students of SD Negeri 008 Pematangsemut by the number of students 23 people, consisting of 11 male students and 12 female students. Design of this research is the Classroom Action Research (CAR). The study was conducted in two cycles, with four times the learning and twice daily tests. Instruments of data collection in this study is the observation sheet activities of teacher and student activity and achievement test. Once applied cooperative learning model Numbered Head Together (NHT), the research results show that the activity of teachers has increased from 58.33% in the first cycle to 87.50% in the second cycle. Activities of students also increased from 54.17% in the first cycle to 83.33% in the second cycle. The implementation of cooperative learning model NHT also improve student learning outcomes of the average value of 62.13 increased by 0.36% to 82.27 on the second cycle. The completeness classically increased from baseline of 40% to 70% in the first cycle, then increased again to 95% in the second cycle. Based on these results it can be concluded that the application of cooperative learning model Numbered Head Together (NHT) can improve learning outcomes IPS fifth grade students of SD Negeri 008 Pematangsemut.Key Words: Cooperative type Numbered Head Together (NHT), Learning Outcomes IPS.